Saccadic Alterations in Severe Developmental Dyslexia - Stefano Pensiero; Agostino Accardo; Paola Michieletto; Paolo Brambilla (Case Reports in Neurological Medicine)
It is not sure if persons with dyslexia have ocular motor deficits in addition to their deficits in rapid visual information processing. A 15-year-old boy afflicted by severe dyslexia was submitted to saccadic eye movement recording. Neurological and ophthalmic examinations were normal apart from the presence of an esophoria for near and slightly longer latencies of pattern visual evoked potentials. Subclinical saccadic alterations were present, which could be at the basis of the reading pathology: (1) low velocities (and larger durations) of the adducting saccades of the left eye with undershooting and long-lasting postsaccadic onward drift, typical of the internuclear ophthalmoplegia; (2) saccades interrupted in mid-flight and fixation instability, which are present in cases of brainstem premotor disturbances.